2016
DOI: 10.1016/j.bpj.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin Assembly Regulated by Adaptor Proteins in Coarse-Grained Models

Abstract: The assembly of clathrin triskelia into polyhedral cages during endocytosis is regulated by adaptor proteins (APs). We explore how APs achieve this by developing coarse-grained models for clathrin and AP2, employing a Monte Carlo click interaction, to simulate their collective aggregation behavior. The phase diagrams indicate that a crucial role is played by the mechanical properties of the disordered linker segment of AP. We also present a statistical-mechanical theory for the assembly behavior of clathrin, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…59 In previous work, we explored the effect of sites located at the ankle and at the knee on cage assembly in solution, establishing that both possibilities permit AP-regulated clathrin aggregation. 51 Our study revealed that the mechanical properties of the AP linker region play a crucial role in regulating the assembly mechanism. Here, the β 2 bead binds to the clathrin ankle only, as this is the accepted site in the current literature.…”
Section: Interaction With Clathrinmentioning
confidence: 77%
See 4 more Smart Citations
“…59 In previous work, we explored the effect of sites located at the ankle and at the knee on cage assembly in solution, establishing that both possibilities permit AP-regulated clathrin aggregation. 51 Our study revealed that the mechanical properties of the AP linker region play a crucial role in regulating the assembly mechanism. Here, the β 2 bead binds to the clathrin ankle only, as this is the accepted site in the current literature.…”
Section: Interaction With Clathrinmentioning
confidence: 77%
“…In several preceding studies, we modelled clathrin as curved, rigid patchy particles to study the in vitro self-assembly of clathrin cages in bulk through Monte Carlo and Brownian dynamics simulations. [47][48][49][50][51] We here provide a brief description of the model and refer the reader to our previous publications for a more detailed discussion. The model triskelion consists of three identical legs stemming from a central "hub" (h) at a "pucker" angle χ relative to the normal vectorn h along the threefold rotational symmetry axis of the particle, see Fig.…”
Section: The Clathrin Modelmentioning
confidence: 99%
See 3 more Smart Citations